Efektivitas Program Kampung Keluarga Berencana (KB) Terhadap Pemberdayaan Masyarakat Di Kota Tangerang Selatan Tahun 2026 - Pratiwi Cahya Wardhani; Ocha Yozi Fauzia (Jurnal Obstretika Scientia, 2026)
The National Population and Family Planning Board introduced a new program called the Family Planning Village. There are eight Family Planning Village areas in South Tangerang City that were established in 2017, and until now no evaluation has been conducted regarding the implementation of this program. This study aimed to determine the effectiveness of the Family Planning Village program on community empowerment in South Tangerang City. Methods: This study used a quasi-experimental pretest and posttest design with a sample of 109 respondents living in the Family Planning Village areas of Pondok Kacang Timur and Ciputat Subdistricts. The sampling technique used was Cluster Random Sampling. Data were analyzed using the Dependent T-Test with α = 0.05. Results: Community empowerment before and after the implementation of the Family Planning Village program showed a p-value of 0.337. The average age of respondents was 36.5 years (p-value = 0.000), more than half had a low educational background (68.8%) with a p-value of 0.000, 77.1% of respondents were unemployed with a p-value of 0.011, and the average monthly income was 2,536,697 IDR with a p-value of 0.000. There was no significant difference in community empowerment before and after the implementation of the Family Planning Village program. Conclusion : The Family Planning Village program in South Tangerang City was not effective in empowering the community. However, the most dominant variable was income. Suggestion: The South Tangerang Government should provide financial support as well as adequate facilities and infrastructure to implement this program effectively so that its objectives can be achieved.